2016
DOI: 10.5101/nbe.v7i4.p160-168
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles Using Cosmos Sulphureus and Evaluation of Their Antimicrobial and Antioxidant Properties

Abstract: The present study intended to synthesize, characterize silver nanoparticles (AgNPs) using Cosmos sulphureus (Cs) aqueous leaf extract and their antimicrobial and antioxidant activities. The UV-vis spectrophotometer exhibited an absorbance peak around 430-440 nm with color intensity from yellow to reddish brown after 4 days. SEM and EDX analysis showed AgNPs were pure and polydispersed and the size were ranging from 55 to 80 nm. XRD revealed that the nanoparticles were cubic and face centered in shape and the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Our results are supported by different reported studies with sharp peaks at 3 keV in EDX (34)(35)(36)(37). As these AgNPs were synthesized with different plant materials, Acacia nilotica, Citrus sinensis, Cosmos Sulphureus, and Dracocephalum moldavica, still the resultant Ag availability was determined at around 3 keV through EDX analysis.…”
Section: Edx Detectionsupporting
confidence: 92%
“…Our results are supported by different reported studies with sharp peaks at 3 keV in EDX (34)(35)(36)(37). As these AgNPs were synthesized with different plant materials, Acacia nilotica, Citrus sinensis, Cosmos Sulphureus, and Dracocephalum moldavica, still the resultant Ag availability was determined at around 3 keV through EDX analysis.…”
Section: Edx Detectionsupporting
confidence: 92%
“…According to the analysis, the extract P1-L-M, obtained from leaves of Population 1 with 70% methanol, exhibited the strongest DPPH • radical scavenging activity with an IC 50 value of 0.196 ± 0.03 mg/mL ( Table 2 ). Previous studies reported an IC 50 of 135.53 ± 1.78 μg/mL in aqueous leaf extract [ 33 ] and an IC 50 of 129.21 μg/mL in ethyl acetate fractions from C. sulphureus [ 34 ]. The concentration required to inhibit the DPPH • radical shown by the extracts of C. sulphureus was similar to that previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…Помимо эфирных масел, в литературных источниках описано наличие в космее дваждыперистой других классов соединений, потенциально обладающих антимикробной активностью (флавоноиды, фенолокислоты, дубильные вещества и др.). Однако не описано экспериментальных исследований антимикробной активности суммарных водных и водно-спиртовых экстрактов космеи дваждыперистой [Menut et al, 2000;Malaka et al, 2015;Saleem et al, 2019].…”
Section: Introductionunclassified